Authenticity as Best-Self: The Experiences of Women in Law Enforcement - Jacobs, Rochelle; Barnard, Antoni (Frontiers in Psychology, 2022)
Law enforcement poses a difficult work environment. Employees’ well-being is uniquely taxed in coping with daily violent, aggressive and hostile encounters. These challenges are compounded for women, because law enforcement remains to be a male-dominated occupational context. Yet, many women in law enforcement display resilience and succeed in maintaining a satisfying career. This study explores the experience of being authentic from a best-self perspective, for women with successful careers in the South African police and traffic law enforcement services. Authenticity research substantiates a clear link between feeling authentic and experiencing psychological well-being. The theoretical assumption on which the study is based, holds that being authentic relates to a sense of best-self and enables constructive coping and adjustment in a challenging work environment. A qualitative study was conducted on a purposive sample of 12 women, comprising 6 police officers and 6 traffic officers from the Western Cape province in South Africa. Data were gathered through narrative interviews focusing on experiences of best-self and were analyzed using interpretive phenomenological analysis. During the interviews participants predominantly described feeling authentic in response to work-related events of a conflictual and challenging nature. Four themes were constructed from the data to describe authenticity from a best-self perspective for women in the study. These themes denote that the participating women in law-enforcement, express feeling authentic when they present with a mature sense of self, feel spiritually congruent and grounded, experience self-actualization in the work-role and re-align to a positive way of being. Women should be empowered towards authenticity in their world of work, by helping them to acquire the best-self characteristics needed for developing authenticity.